2007
DOI: 10.1121/1.2436632
|View full text |Cite
|
Sign up to set email alerts
|

Parallel capillary-tube-based extension of thermoacoustic theory for random porous media

Abstract: Thermoacoustic theory is extended to stacks made of random bulk media. Characteristics of the porous stack such as the tortuosity and dynamic shape factors are introduced into the thermoacoustic wave equation in the low reduced frequency approximation. Basic thermoacoustic equations for a bulk porous medium are formulated analogously to the equations for a single pore. Use of different dynamic shape factors for the viscous and thermal effects is adopted and scaling using the dynamic shape factors and tortuosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…This result indicates that r 0 should be used instead of r eff for better estimation of heat flow. Other earlier studies [29,31] have demonstrated that two effective radii are necessary to explain the viscous behavior and the thermal behavior in tortuous porous media because the viscous effects are governed by narrower regions of the channel, whereas the thermal effects are determined by wider regions [32,33]. Our experimentally obtained results provide another example representing the need of the effective thermal radius, in addition to the effective viscous radius.…”
Section: Discussionmentioning
confidence: 57%
“…This result indicates that r 0 should be used instead of r eff for better estimation of heat flow. Other earlier studies [29,31] have demonstrated that two effective radii are necessary to explain the viscous behavior and the thermal behavior in tortuous porous media because the viscous effects are governed by narrower regions of the channel, whereas the thermal effects are determined by wider regions [32,33]. Our experimentally obtained results provide another example representing the need of the effective thermal radius, in addition to the effective viscous radius.…”
Section: Discussionmentioning
confidence: 57%
“…The stability of the algorithm has been checked by means of simulated experiments with artificial added noise and bias. For the acoustical problem (no heating), the estimation of the porosity, the tortuosity and the pore's inner radius of the stack/regenerator can be successfully achieved, but the estimation of a fourth parameter may make the algorithm unstable because an additional geometrical parameter would be correlated to the three above mentioned parameters (that is the reason why we did not account for the dynamic shape factors [26] in the description of acoustic propagation through the stack).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In the following, we derive the governing equations from which these T-matrices can be determined. Considering a piece of stack along which the temperature distribution T (x) is assigned, the extension of Rott's theory [14] to porous media proposed by Roh et al [26] can be used to derive the relationship between the complex amplitudes of acoustic pressure and volume velocity.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Roh and Raspet [26] developed thermoacoustic theories for a random porous medium. Their theories included development of thermal and viscous functions, wave, and temperature distribution equation.…”
Section: Introductionmentioning
confidence: 99%